Institutional Reforms in the European Union From the Perspective of a Candidate Country for Membership (Selected Macedonian Experiences and Effects) - Spasenovski, Aleksandar (Maastricht 30: A Central European Perspective, 2025)
The paper ‘Institutional Reforms in the European Union from the Perspective of a Candidate Country: Selected Macedonian Experiences and Effects’ focuses on the foreign and defense policy of North Macedonia, analyzing its path to independence and integration into international institutions. Emphasis is placed on the role of the European Union and NATO in shaping Macedonian policy, as well as on public perceptions of achievements and challenges in these areas. The research utilizes data from public opinion surveys, revealing citizens’ perspectives on the progress and setbacks in foreign and defense policies, as well as their expectations for the future. The findings highlight the impact of prolonged delays in EU accession on rising Euroscepticism and propose measures to strengthen EU decision-making processes,prevent abuses by member states, and foster more efficient integration processes. Keywords: North Macedonia, European integrations, Foreign affairs, Independence